Japan’s Shift to the Right: Computational Propaganda, Abe Shinzō’s LDP, and Internet Right-Wingers (Netto Uyo) - Schäfer, Fabian (Asia-Pacific Journal : Japan Focus, 2022)
In recent years, academic research and investigative reports have brought to light several cases of computational propaganda (i.e. orchestrated attempts to manipulate public opinion or the outcome of elections via social media), as well as proof that filter algorithms amplify right-wing conservative content on Japanese social media. Piecing together the scattered pieces of a puzzle, this article summarizes recent findings from various disciplines and provides an overview of the mechanisms and potential scope of computational propaganda in politics. Although there is no conclusive evidence of who is behind this anonymous activity, an analysis of these findings demonstrates increasing circumstantial evidence that certain factions of the LDP are actively using computational propaganda, either by commissioning external contractors or through its online support group, J-NSC, thereby condoning and appealing to anonymous Internet right-wingers (netto uyo). The concluding discussion assesses the effects and consequences of computational propaganda on the political sphere in contemporary Japan.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Computational propaganda; Dappi; Liberal Democratic Party (LDP); Populism; Social media